Improving The Ability To Recognize Age Of Children Early Through Media Wheels Rotate In Group A At Tk Dharma Wanita Sugihwaras Temple: Meningkatkan Kemampuan Mengenal Lambang Bilangan Anak Usia Dini Melalui Media Roda Putar Pada Kelompok A - Ferizca Tyas Wijayanti (Universitas Muhammadiyah Sidoarjo, 2020)
The Capability to recognize number symbols plays an important role in children's lives because with the ability to recognize number symbols we can calculate something. The activity of recognizing number symbols is an activity to count which is carried out using various media such as, Spining Whells. The purpose of this study is to improve the ability to recognize early childhood number symbols in group A at TK DHARMA WANITA SUGIHWARAS CANDI. This type of research is classroom action research. Based on the data analysis carried out, it was concluded that the children's fine motor skills in the pre-cycle obtained an average value of 54.70% while the first cycle obtained a percentage of 66.66% which meanthat it was not optimal. Then give action in the second cycle, the percentage of the average value of the child becomes 82.05%, so that from the average gain in the first cycle and second cycle there is an increase of 15.39%. The conclusion of this study is that through spinning whells can improve the ability to recognize the symbols of numbers.